Double-Tee Members in Axial Compression - Arber, Leigh; Wang, Meng; McManus, Pat (Engineering Journal, 2015)
This paper presents tabulated compressive strengths of double-tee members, which are comprised of two WT members oriented with their flanges back to back (referred to as "2WTs"ť or "double WTs"ť hereafter). The benefits and typical use of these members are described, including schematic details of connection designs. All WT members built from the WT7 and WT6 series are included in the table, which gives available strengths in both ASD and LRFD. Slenderness effects and the effects of shear deformations of intermediate connectors are taken into account.